Development and characterization of chlorophyll-amended montmorillonite clays for the adsorption and detoxification of benzene. (1st August 2022) - Rivenbark, Kelly J.; Wang, Meichen; Lilly, Kendall; Tamamis, Phanourios; Phillips, Timothy D.
Highlights: Novel chlorophyll-amended clays were developed to remediate and detoxify benzene. Chlorophyll-amended clays showed favorable binding profiles and thermodynamics. Molecular simulations suggested van der waals forces as the main adsorption mechanism. Chlorophyll-amended clays protected L. minor and C.elegans against benzene toxicity. Abstract: After disasters, such as forest fires and oil spills, high levels of benzene (> 1 ppm) can be detected in the water, soil, and air surrounding the disaster site, which poses a significant health risk to human, animal, and plant populations in the area. While remediation methods with activated carbons have been employed, these strategies are limited in their effectiveness due to benzene's inherent stability and limited retention to most surfaces. To address this problem, calcium and sodium montmorillonite clays were amended with a mixture of chlorophyll (a) and (b); their binding profile and ability to detoxify benzene were characterized using in vitro, in silico, and well-established ecotoxicological (ecotox) bioassay methods. The results of in vitro isothermal analyses indicated that chlorophyll-amended clays showed an improved binding profile in terms of an increased binding affinity (Kf = 668 vs 67), increased binding percentage (52% vs 11%), and decreased rates of desorption (28% vs 100%), compared to the parent clay. In silico simulation studies elucidated the adsorption mechanism and validated that the addition of the chlorophyll to the clays increased the adsorption of benzene through Van der Waals forces (i.e., aromatic π-π stacking and alkyl-π interactions). The sorbents were also assessed for their safety and ability to protect sensitive ecotox organisms ( Lemna minor and Caenorhabditis elegans ) from the toxicity of benzene. The inclusion of chlorophyll-amended clays in the culture medium significantly reduced benzene toxicity to both organisms, protecting C. elegans by 98–100% from benzene-induced mortality and enhancing the growth rates of L. minor . Isothermal analyses, in silico modeling, and independent bioassays all validated our proof of concept that benzene can be sequestered, tightly bound, and stabilized by chlorophyll-amended montmorillonite clays. These novel sorbents can be utilized during disasters and emergencies to decrease unintentional exposures from contaminated water, soil, and air. Graphical abstract: Image, graphical abstract